Analisis Butir Soal Teknik Dasar Otomotif Berbasis Diagnostik Kognitif dengan Anates Versi 4.02 - Dwi Jatmoko; Basuki Basuki; Agung Pambudi; Kuntho Alief Setiyono; Beni Nugroho (JURNAL RISET RUMPUN ILMU PENDIDIKAN, 2025)
The purpose of this study was to determine the quality of the Odd Semester Final Summative Questions for the Automotive Basic Engineering Subject for Class X SMK TKM Pertambangan Kebumen using the Anates V4 Application. The exam question data, answer keys, and all students' answers were collected through data collection documentation techniques. Furthermore, using the Anates version 4.02 program, item analysis will be carried out to assess the validity, reliability, level of difficulty, discriminatory power, and effectiveness of distractors. This research method is quantitative descriptive research, the data analyzed is not used to accept or reject the hypothesis; instead, the results of the analysis show a description of the observed symptoms, which are represented by numbers or coefficients between variables. The results showed that 95% of the odd semester final summative questions for the Automotive Basic Engineering subject for Class X SMK TKM Pertambangan Kebumen using the Anates V4 Application had validity, with 5% being invalid. For reliability, the questions had a reliability coefficient of 0.78, which indicated that it had a high coefficient. Furthermore, based on the level of difficulty, 2% were included in the easy category; 40% were included in the moderate category; 55% are in the difficult category; and 3% are in the very difficult category. In terms of discrimination power, 25% are in the good category; 57% are in the sufficient category; and 18% are in the poor category. All distractors function well on 90% of the questions.